2022
DOI: 10.1002/bio.4243
|View full text |Cite
|
Sign up to set email alerts
|

Development of highly selective fluorescent ferrocenyl‐iminopyridine chemosensor for biologically relevant Fe3+

Abstract: Design, synthesis, characterization, and ion detection studies of two ferroceneappended Schiff bases namely N-(2-[ferrocenylamino]ethyl)-5-nitropyridin-2-amine(1) and ferrocenylamino-1H-imidazole-4-carboxamide (2) been reported. Both the chemosensors have been thoroughly characterized using Fourier transfer infrared, 1 H and 13 C nuclear magnetic resonance, high resolution mass spectrometry, and ultraviolet/visible (UV/visible) and fluorescence spectral techniques. Probes 1 and 2 were designed with the aim of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The binding constant (Ks) was investigated by using the nonlinear equation via a plot between the emission intensity and the Zn(II) concentration. The binding constant value ( K s ) was found to be 1.30 × 10 6 M –1 for 1- Zn(II) (Figure a), 8.0 × 10 5 M –1 for 2- Zn(II) (Figure b), and 1.32 × 10 6 M –1 for 3- Zn(II) (Figure c) systems …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The binding constant (Ks) was investigated by using the nonlinear equation via a plot between the emission intensity and the Zn(II) concentration. The binding constant value ( K s ) was found to be 1.30 × 10 6 M –1 for 1- Zn(II) (Figure a), 8.0 × 10 5 M –1 for 2- Zn(II) (Figure b), and 1.32 × 10 6 M –1 for 3- Zn(II) (Figure c) systems …”
Section: Resultsmentioning
confidence: 98%
“…The binding constant value (K s ) was found to be 1.30 × 10 6 M −1 for 1-Zn(II) (Figure 5a), 8.0 × 10 5 M −1 for 2-Zn(II) (Figure 5b), and 1.32 × 10 6 M −1 for 3-Zn(II) (Figure 5c) systems. 41 To investigate the limit of detection (LOD) values, we added Zn(II) ions with varying concentrations (10 −2 M to 10 −12 M) to the solution of 1−3 (10 μM) to evaluate the sensitivity with the Zn(II) ion. A graph between the concentration and fluorescence intensity exhibits a significant change at 10 −6 M for both 1-Zn(II) and 2-Zn(II) while at 10 −7 M for 3-Zn(II), (Figure S17).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Furthermore, a novel dual-mode (colorimetry and fluorometry) optical approach for qualitative and quantitative identification of iron (II) and gallic acid (GA) using the Fenton reaction-TMB method was developed by Qi et al [34]. These studies established the high selectivity and sensitivity of the dual-mode assay towards recognition of iron (II) and GA. Sharma et al [35] reported the fabrication, characterization, design, and ion identification of different ferrocenyl-Schiff bases (1) and ( 2). The results suggested that probe 1 displayed a very selective fluorescence detection of Fe 3+ ions, whereas probe 2 did not display any specific response towards anions and cations.…”
Section: Overview Of Published Researchmentioning
confidence: 99%
“…4,5 To analyze and determine CN − , various methods such as ion chromatography, 6 titrimetric analysis, 7 and electrochemical methods 8 the selective sensing of CN − is highly imperative and attractive with regard to chemical and physical methods. 4 Moreover, advancements in supramolecular fluorescent materials 9 are increasing due to their fascinating characteristics, such as high sensitivity, naked-eye detection, and fast response time. 10−12 Novel fluorescent materials based on nanofibers, dot formation, polymers, and metallogels involving different sensing mechanisms for detection of toxic CN − find vast applications in various fields.…”
Section: ■ Introductionmentioning
confidence: 99%